(untitled) (Journal of the College of Basic Education, 2022)
The American presidency is one of the institutions created by the American mind to achieve meaningsDemocratic government according to the presidential model as one of the types of representative system that is based on the principleSeparation of powers and its essence is the independence of the judiciary and the independence of the legislative and executive branchesand restricting the executive power to the elected president of the state, and this is contrary to the systemParliament in which the legislative and executive powers are partially separate and each ownsThe means by which you can hold others accountable and monitored. It can also be adopted in countriesMonarchy and republic alike, while the presidential system can only be introduced in republican statesThe reason for this is due to the concentration of the executive authority under this system in the hands of the head of state alone.